HUBUNGAN POLA ASUH ORANGTUA DENGAN PERKEMBANGAN BAHASA ANAK USIA PRASEKOLAH DIPAUD SE-MATUARI DESA LAIKIT KABUPATEN MINAHASA UTARA - Ollo, Yulista (Journal Of Community & Emergency, 2024)
The stage of development and language skills of children at preschool age is very important. Given that children’s language development occurs most rapidly between the ages of 2-5 years. Vocabulary increased from 50 - 100 to 2000 more. The most critical for development occurs between the ages of 2-4 years. Language ability is an indicator of all child development. Early detection of language development delays will help in overcoming language delays in pre-school age children so as to minimize difficulties in the child’s learning process when entering school age. preschool age children in PAUD in Matuari Laikit Village, North Minahasa Regency. This research is an analytical descriptive type using a cross sectional study that is descriptive analytic in October 2022 and the research location is in Early Childhood Education in Matuari Laikit Village, North Minahasa Regency. The sampling technique is total sampling. The statistical test used is statistical test. "Chi-square" with 95% confidence if . The results showed that the P value = 0.009 while the value of = 0.05 so that the P value = 0.001 < = 0.05. Thus Ho is rejected and H1 is accepted, so there is a relationship between parenting patterns and language development of preschool children in PAUD in Matuari, Laikit Village, North Minahasa Regency. Conclusion From the results of the study The results of the research on parenting patterns in PAUD in Matuari, Laikit Village, North Minahasa Regency are more democratic than authoritarian. The results of the research on the language development of preschool age children in PAUD in Matuari Laikit Village, North Minahasa Regency, were better than less. Suggestions in this study are as information material for the results of this study into consideration for Laikid Village to be able to find out how to overcome the problem of language development for preschool age children.